2011
DOI: 10.1016/j.njas.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Preference of laboratory rats for food based on wheat grown under organic versus conventional production conditions

Abstract: a b s t r a c tThere is extensive evidence that rats are able to sense toxicants and essential nutrients in their food and avoid foods that contain these substances. This ability was employed to assess whether the two major management factors soil fertility management and crop protection affected the food preferences of laboratory rats. Samples of wheat grown in 2005 and 2007 under four combinations of these management factors in the Nafferton Factorial Systems Comparison at Northumberland UK were used as expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Visceral fat and lipid accumulation in adipocyte and obese rats were suppressed by TV, thus preventing obesity. Therefore, our animal experiments supported by the conclusions [64,65] establish that BBRDM-produced tomatoes are absolutely safe for consumption, considering the rat model as a surrogate for the human physiological system. To the best of our knowledge, this study represents the first animal-model food safety evaluation of tomatoes cultivated with an experimental organic fertilizer.…”
Section: Maximumsupporting
confidence: 60%
See 1 more Smart Citation
“…Visceral fat and lipid accumulation in adipocyte and obese rats were suppressed by TV, thus preventing obesity. Therefore, our animal experiments supported by the conclusions [64,65] establish that BBRDM-produced tomatoes are absolutely safe for consumption, considering the rat model as a surrogate for the human physiological system. To the best of our knowledge, this study represents the first animal-model food safety evaluation of tomatoes cultivated with an experimental organic fertilizer.…”
Section: Maximumsupporting
confidence: 60%
“…This capacity was applied to judge whether the two major agronomic factors, soil fertility management and crop protection had an effect on the food preferences of laboratory rats [64]. Authors recorded a positive influence of organic fertilization on food choice.…”
Section: Maximummentioning
confidence: 99%
“…46,47 A more recent factorial study reported that the preference for organic wheat was linked to organic fertilization and crop protection regimes. 48 Although there were significant differences in the concentrations of CCC and Cd between feeds, there were no negative correlations between the concentrations of these potentially deleterious compounds and daily feed intake; in fact, feed intake was correlated positively with Cd concentrations in feeds. However, there was a significant negative correlation between polyphenol concentrations and feed intake, a result that supports previous studies showing that a high content of certain phenolic a Data are presented as the mean ± SE with ANOVA P-values.…”
Section: ■ Discussionmentioning
confidence: 88%
“…There are, to our knowledge, no factorial studies in which the relative effect, and interactions between, contrasting fertilization and crop protection regimes (used in organic and conventional farming) on feed intake was compared. However, some feed preference studies (in which rats were provided with access ad libitum to both organic and conventional feeds simultaneously) have shown that rats prefer organic over conventional crops or feeds and speculated that this preference may be due to rats sensing taste or deleterious compounds (e.g., pesticides) in conventionally produced feeds. , A more recent factorial study reported that the preference for organic wheat was linked to organic fertilization and crop protection regimes . Although there were significant differences in the concentrations of CCC and Cd between feeds, there were no negative correlations between the concentrations of these potentially deleterious compounds and daily feed intake; in fact, feed intake was correlated positively with Cd concentrations in feeds.…”
Section: Discussionmentioning
confidence: 99%